2021
DOI: 10.1002/tpg2.20086
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics and genome‐wide association studies provide insights into the influence of selective breeding on genetic variation in lettuce

Abstract: Genetic diversity is an important resource in crop breeding to improve cultivars with desirable traits. Selective breeding can lead to a reduction of genetic diversity. However, our understanding on this subject remains limited in lettuce (Lactuca sativa L.). Genotyping-by-sequencing (GBS) can provide a reduced version of the genome as a cost-effective method to identify genetic variants across the genome. We genotyped a diverse set of 441 lettuce accessions using the GBS method. Phylogenetic and population ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 58 publications
3
16
1
Order By: Relevance
“…Therefore, our sequence data could be used in subsequent analysis. Moreover, we obtained a transition/transversion ratio of 3.51, which was higher than those obtained for common bean (1.27) [ 44 ], apricot (1.78–1.79) [ 51 ], and lettuce (2.10) [ 52 ], but lower than that previously reported for tea (4.02) [ 15 ]. Thus, transitions better tolerated the natural resistance and might have consisted of synonymous mutations in protein-coding sequences [ 53 ].…”
Section: Discussioncontrasting
confidence: 72%
“…Therefore, our sequence data could be used in subsequent analysis. Moreover, we obtained a transition/transversion ratio of 3.51, which was higher than those obtained for common bean (1.27) [ 44 ], apricot (1.78–1.79) [ 51 ], and lettuce (2.10) [ 52 ], but lower than that previously reported for tea (4.02) [ 15 ]. Thus, transitions better tolerated the natural resistance and might have consisted of synonymous mutations in protein-coding sequences [ 53 ].…”
Section: Discussioncontrasting
confidence: 72%
“…Our results showed that another feature of Baekdadagi-specific genetically diverse genomic regions is maintenance of genetic diversity; however, this diversity was not distributed evenly across the cucumber genomes. These results are consistent with selective sweep events which happened during domestication and modern breeding in mung bean and lettuce [38,39]. Putative selective sweep regions of both crops were also not distributed evenly.…”
Section: Discussionsupporting
confidence: 81%
“…We generated 255.2 Gb clean data from 253 tea accessions with an average of 1.00 Gb clean data per accession, and identi ed 112,072 high-quality SNPs, which was higher than the data reported in the previous study. Moreover, the transition/transversion rate was 3.51, which was higher than those in common bean (Phaseolus vulgaris L.) (1.27) [37], apricot (1.78~1.79) [39] and lettuce (2.10) [40] and lower than the previous report of tea plant (4.02) [14]. This result suggested that transitions were better tolerated the natural resistance, which could be that they were synonymous mutations in protein-coding sequences [41].…”
Section: Genetic Diversity Of Cultivated-type Tea Plantsmentioning
confidence: 75%